Uric acid and neurodegenerative diseases: finding a predictor of cognitive decline: Ácido úrico y enfermedades neurodegenerativas: encontrando un predictor del deterioro cognitivo | 尿酸与神经退行性疾病：寻找认知衰退的预测指标 - Pernia, Patricia (2024)
Uric Acid, a potent endogenous antioxidant, has recently been investigated for its potential relationship with neurodegenerative diseases. This letter proposes that uric acid could serve as a predictive marker of cognitive decline in neurodegenerative conditions. Recent studies suggesting a correlation between elevated uric acid levels and a lower risk of cognitive decline are reviewed, advocating for further research to confirm these findings. Additionally, the clinical implications of using uric acid as a potential biomarker in neurological practice are discussed.